KESADARAN MEREK DAN MINAT TERHADAP PRODUK SYARIAH PADA PT. BANK. SUMUT SYARIAH CABANG SIBOLGA - Kaharuddin Kaharuddin (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study explains brand awareness factors and interest in Islamic products at PT. Bank. North Sumatra Syariah The research methodology used is a descriptive quantitative approach. Data collection was carried out using a questionnaire that had been created based on predetermined research indicators. Implementation of this research by distributing questionnaires to the public who will or have ever made a purchase transaction at PT. Bank. North Sumatra Syariah Sibolga Branch The location of this research is Sibolga. In this study used a sample of 100 responses. The results of this study which shows that the independent variable (X1) Brand Awareness has a t-value of 5.596 and a value of Sig. The value of t_count> t_table is 5,596> 1,984 and Sig. <0.05 which is 0.000 <0.05 and the independent variable (X2) Interest has a t-value of 5.273 and Sig. 0,000. The value of ð‘¡ â„Žð‘–ð‘¡ð‘¢ð‘›ð‘”> ð‘¡ ð‘¡ð‘Žð‘ð‘’ð‘™ is 5.273> 1.984 and the value of ð‘†ð‘–ð‘”. <0.05 which is 0,000 <0.05, from these results it can be concluded that of the two variables can be accepted and shows the effect on Islamic products at PT. Bank. North Sumatra Syariah Sibolga Branch.